Factors Affecting Graduate Degree Pursuit for BSN-Prepared Filipino and Filipino American Nurses Working in the United States - Nagtalon-Ramos, Jamille Kristine (University of Pennsylvania, 2017)
Although Filipino and Filipino American nurses represent an impressive share of the nursing workforce, they are not well represented in advanced practice, faculty, and executive leadership positions. Obtaining a graduate degree in nursing has the potential to open a wider range of opportunities to meet the healthcare demands of a population that is growing older, and increasingly becoming more diverse. The purpose of this study was to examine the factors affecting graduate degree pursuit for BSN-prepared Filipino and Filipino American nurses working in the United States. This study provides an in-depth examination into intergenerational perspectives from 33 Filipino and Filipino American nurses from 14 states. Ricoeur’s hermeneutical phenomenology was utilized as an interpretive approach and the theoretical underpinnings of career construction theory served as a framework. This study revealed that the determination to provide a better life for their family and a commitment to advancing the profession were incentives to pursuing a graduate degree. In addition, having a reliable network of colleagues and peer mentors was essential to persisting in their programs. Across all generations, finances were a major barrier to educational attainment, specifically for first-generation participants who prioritized sending money back to their family in the Philippines. Other factors were related to English as a second language, communication styles, experiencing discrimination, lack of knowledge of available graduate programs, approaching the age of retirement, friction between generations, and perceived discrimination. Exposure to advanced practice registered nurses in the workforce was a disincentive for some participants and was inspiring to others. These factors were not independent of each other and their impact fluctuated over time. The decision to pursue an advanced nursing degree depended upon the individual’s determination that the return on investment of a graduate degree outweighed the sum of all their responsibilities and obligations. Findings from this research can help the Filipino community and professional nursing organizations, higher education faculty and staff, and healthcare system leaders in developing strategic plans to help Filipino and Filipino American nurses overcome barriers and to facilitate robust pathways for those who intend to advance their educational goals and professional nursing careers.